The Impact of Adjectives in Descriptive Writing Among Second Language Learners (A Study on Grade Ten Students of Km/Str/ Al-Hidaya Maha Vidyalaya, Chawalakade) - M.T.M. Azmy; M.J Fathima Sujani; M.R Rishad Muhammed; MB. Nowzath (Beginner: Journal of Teaching and Education Management, 2024)
This research delves into the impact of descriptive writing proficiency among grade ten students in Al-Hidaya Maha Vidyalaya where English is taught as a second language. This research aims to analyze the use of adjective in writing descriptive text among grade ten students. The objectives of the study are; to identify any challenges or barriers faced by grade 10 students in incorporating adjectives into their descriptive writing compositions, to develop a personal writing style that utilizes adjectives effectively to create vivid and engaging descriptive passages, to reflect on personal growth in descriptive writing skills through self-assessment and goal setting, to identify the types of adjective and apply suitable adjectives in the appropriate place. Data collection methods include interviews, questionnaires, pre-tests, and post-tests conducted on a sample of 30 students. Results indicate a notable improvement in descriptive writing proficiency from pre-test scores (33.33%) to post-test scores (100%). Notably, the study emphasizes the significance of innovative teaching techniques to enhance students' descriptive writing skills and overall language competence. The teachers should give more motivations to the students in teaching learning process about applying adjective in writing descriptive text effectively.